The Effect Of Nutrition Education On Food Waste In Patients With Diabetes Mellitus - Meitris, Indriana; Sri Rezeki Pettalolo; Masfufah, Masfufah (Sean Institute, 2024)
Background: Food waste is an indicator of the success of nutrition services in hospitals. If food waste is >20% in every feeding then this shows that nutrition services in the hospital have failed. One way to reduce food waste is by providing education. And Diabetes Mellitus is the biggest contributor to food waste during hospitalization. The purpose of the study was to determine the effect of providing nutrition education on food waste in patients with diabetes mellitus at RSUD Undata, Central Sulawesi Province. Methods: The type of research used is quantitative with experimental method of pre-experiment design one group pretest-posttest. The population of this study were patients with diabetes mellitus who were hospitalized at RSUD Undata, with a sample size of 30 respondents aged 18 to 55 years. The data collection technique used the method of weighing food waste. Research Results: Of the 30 respondents, the percentage of food waste before being given nutrition education was (>20%) with each type of staple food 43%, animal side dishes 38.3%, vegetable side dishes 37.4% and vegetables 56.3%. After being given education, the percentage of food waste decreased, namely (<20%) the type of staple food 5.6%, vegetable side dishes 13.3%, animal side dishes 5% and vegetable 10.3%. Conclusion: There is an effect on the provision of nutrition education on food waste in patients with diabetes mellitus with a significance value >0.05 on the types of staple food, animal side dishes, vegetable side dishes and vegetables. While nutrition education on the rest of fruit food has no effect with a significance value >0.05.